Charge Carrier Dynamics at Heterojunction of Semiconductor Nanoheterostructures for Photocatalytic Solar Fuel Generation - Kai‐An Tsai; Jui‐Cheng Chang; Ying‐Chih Pu (Advanced Energy & Sustainability Research, 2025)
This review summarizes the investigation of semiconductor nanoheterostructures (NHSs) aimed at enhancing the efficiency of solar fuel generation through various time‐resolved spectroscopic techniques, including transient absorption spectroscopy (TAS), time‐resolved photoluminescence, and in situ TAS. These time‐resolved spectroscopies provide insights into the mechanisms of exciton and charge carrier dynamics at the heterojunctions of optimized semiconductor NHSs. The significance of these techniques underscores the necessity for designing effective photocatalysts and photoelectrodes for applications in photocatalytic water splitting and carbon dioxide reduction. Finally, the current challenges and future directions for studying charge carrier dynamics in semiconductor NHSs for photocatalytic solar fuel generation are outlined and discussed.